Bactericidal effect of Er: YAG laser combined with sodium hypochlorite irrigation against Enterococcus faecalis deep inside dentinal tubules in experimentally infected root canals. Issue 2 (1st February 2016) - Cheng, X.; Chen, B.; Qiu, J.; He, W.; Lv, H.; Qu, T.; Yu, Q.; Tian, Y.
Abstract : This study evaluated the bactericidal effect of Er:YAG laser radiation combined with sodium hypochlorite (NaOCl) irrigation in the treatment of Enterococcus faecalis deep inside dentinal tubules. The Er:YAG laser was activated, respectively, at 0.3, 0.5 and 1.0 W for either 20 or 30 s; 52.5 g l − 1 NaOCl and normal saline were used for the control groups. Root canals before and after treatments were examined using scanning electron microscopy (SEM). Bacterial reductions both on the root canal walls and at 100, 200, 300, 400 and 500 μm inside the dentinal tubules were analysed using a one-way analysis of variance. SEM results showed that the Er:YAG laser combined with NaOCl disinfected the dentinal tubules from 200 to over 500 μm depth as irradiation power and time increased. This combination killed significantly more bacteria than both the negative control group at each level tested and the positive control group at 300, 400 and 500 μm inside the dentinal tubules. It reached 100 % in all experimental groups, both on the root canal walls and at 100 and 200 μm inside the dentinal tubules. However, at 300, 400 and 500 μm inside the dentinal tubules, only the groups treated with 0.5 and 1.0 W for 30s exhibited no bacterial growth. Of the two groups in which no bacteria were detected at all tested depths, Er:YAG laser irradiation at 0.5 W for 30 s combined with NaOCl irrigation was preferable because of the lower emission power and shorter irradiation time, and may serve as a new option for effective root canal disinfection.